Glass fiber paper for desiccant rotating wheel and preparation method of glass fiber paper

Glass fiber paper prepared by proportioning glass fiber, wood pulp, magnesium oxide and other components solves the problem of existing glass fiber paper being ineffective in long-term dehumidification work and achieves higher strength, adsorption performance and stability It meets the needs of improving industrial performance.

CN119332534APending Publication Date: 2025-01-21JIANGSU HEYAO TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411500598.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing fiberglass paper is difficult to achieve the expected adsorption and dehumidification effects under long-term dehumidification working conditions, and cannot meet the ever-increasing industrial performance needs.

Method used

A high-performance glass fiber paper is prepared by using a ratio of glass fiber, wood pulp, magnesium oxide, polyvinyl alcohol fiber, coconut shell fiber, modified biochar and modified graphene oxide gel. The method includes mixing, stirring, shaping and drying the above components to form glass fiber paper with improved strength, adsorption performance and stability.

Benefits of technology

Improve the strength of glass fiber paper, adsorption performance, and stability in damp heat environment, and meet higher industrial performance needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102487180000081
    Figure BDA0005102487180000081
Patent Text Reader

Abstract

The invention relates to glass fiber paper for a desiccant wheel and a preparation method of the glass fiber paper. The glass fiber paper is prepared from the following components in parts by weight: 60-80 parts of glass fibers, 25-35 parts of wood pulp, 15-25 parts of magnesium oxide, 30-36 parts of polyvinyl alcohol fibers, 22-28 parts of coconut fibers, 20-24 parts of modified charcoal, 14-20 parts of modified graphene oxide gel and 10-12 parts of a dispersing agent. The glass fiber paper has the effect of improving the strength and damp-heat adaptability of the glass fiber paper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of gas dehumidification, and in particular to a glass fiber paper for a dehumidification wheel and a preparation method thereof. Background Art

[0002] Dehumidification rotary machine is an important branch of air conditioning field and a typical representative of temperature control and dehumidification.

[0003] Glass fiber paper is the skeleton material of the dehumidification wheel. It can play the role of dehumidification, adsorption, filtration, etc. It is an important component of the dehumidification wheel. The quality of glass fiber paper will directly determine the adsorption and dehumidification effect of the dehumidification wheel.

[0004] However, with the development of industry, the performance requirements for dehumidification rotors are constantly increasing, and the existing glass fiber paper materials are difficult to meet the needs, especially under long-term dehumidification working conditions, the current glass fiber paper is difficult to achieve the expected effect. Summary of the invention

[0005] In order to improve the performance of glass fiber dehumidification paper, the present application provides a glass fiber paper for a dehumidification wheel and a preparation method thereof.

[0006] The present application provides a glass fiber paper for a dehumidification wheel and a preparation method thereof, which adopts the following technical solutions: In the first aspect, the present application provides a glass fiber paper for a dehumidification wheel, which adopts the following technical solution: A glass fiber paper for a dehumidification wheel comprises the following components in parts by weight: 60-80 parts of glass fiber, 25-35 parts of wood pulp, 15-25 parts of magnesium oxide, 30-36 parts of polyvinyl alcohol fiber, 22-28 parts of coconut shell fiber, 20-24 parts of modified biochar, 14-20 parts of modified graphene oxide gel, and 10-12 parts of dispersant.

[0007] By adopting the above technical scheme, glass fiber paper is prepared by the ratio of the above components. On the one hand, the strength of the prepared glass fiber paper can be effectively improved, and at the same time, the adsorption performance of the glass fiber paper can be further improved. Wood pulp has good paper strength and can effectively improve the strength and breaking performance of the glass fiber paper. Magnesium oxide can further improve the wear resistance and strength of the glass fiber paper, and can have good thermal stability and chemical properties, so that the glass fiber paper can improve the adaptability. Polyvinyl alcohol fiber can improve the overall strength of the system and further improve the connection stability between the components. Coconut shell fiber also has high strength performance, and coconut shell fiber has good moisture resistance, which can further improve the adaptability of glass fiber paper in a humid environment, so as to improve the overall stability of the glass fiber paper. At the same time, modified graphene oxide gel and modified biochar components are added to the system. The modified graphene oxide gel can further improve the strength and stability of the system, and the modified biochar can further improve the adsorption performance of the system.

[0008] Preferably, the modified biochar comprises bamboo chips, calcium chloride and urea.

[0009] By adopting the above technical solution, bamboo chips, as a kind of biochar, have a high carbon content and rich functional groups on the surface, which can promote adsorption. However, the void structure of biochar makes it difficult to further improve its adsorption performance. By treating and activating bamboo chips with calcium chloride and urea, the adsorption performance of bamboo chips can be further improved, thereby further improving the adsorption performance of glass fiber paper.

[0010] Preferably, the modified biochar is prepared by the following method: The bamboo chips are dried, crushed and sieved, placed in a quartz ark, placed in the middle of a tube furnace, nitrogen is introduced, the temperature is increased, and the chips are cooled to obtain treated bamboo chips; anhydrous calcium chloride, treated bamboo chips and ethanol are mixed and stirred to obtain a mixed solution, which is then dried and ground to obtain calcium chloride treated bamboo chips; the calcium chloride treated bamboo chips are mixed with urea, placed in a quartz ark, and then placed in the middle of a tube furnace to perform nitrogen and oxygen treatment to obtain modified biochar.

[0011] By adopting the above technical scheme, bamboo chips are used as raw materials, calcium chloride is used for two-step activation, and nitrogen modification is achieved through the technical means of co-pyrolysis of urea under high temperature environment, so as to further improve the adsorption performance and stability of the prepared biochar. The doping of urea prompts nitrogen atoms to obtain a carbon skeleton in the form of pyridine nitrogen, pyrrole nitrogen and graphite nitrogen, so that the richness of nitrogen functional groups on the surface of biochar is improved. Calcium chloride is used as an activator for modification, thereby preparing modified biochar, which further improves the stability, strength and adsorption of the prepared glass fiber paper.

[0012] Preferably, the mass ratio of the bamboo chips, calcium chloride and urea is 1:1:(0.9-1.1).

[0013] By adopting the above technical solution, the mass ratio of bamboo chips, calcium chloride and urea is preferably within the above range, which can further improve the comprehensive performance of the prepared modified biochar.

[0014] Preferably, the nitrogen and oxygen treatment specifically comprises the following steps: Nitrogen is introduced to heat and maintain for a period of time, then cooled, the nitrogen is turned off, oxygen is introduced, and the constant temperature is maintained for 230-250 minutes, then the oxygen is turned off, nitrogen is introduced again, and the mixture is cooled in a nitrogen-protected atmosphere, and the modified biochar is obtained after being taken out.

[0015] By adopting the above technical scheme, oxygen-containing functional groups are loaded on the surface of the system after oxidation to optimize the physical and chemical properties of biochar, thereby further improving the adsorption performance of biochar; after high-temperature reaction activation, the performance of biochar is optimized by low-temperature air oxidation technology, and after the modified biochar is added, the overall comprehensive performance of glass fiber paper can be further improved.

[0016] Preferably, the graphene oxide gel comprises graphene oxide and a modifier.

[0017] By adopting the above technical scheme, graphene oxide has a two-dimensional planar structure and a large specific surface area, and has epoxy functional groups such as hydroxyl, epoxy and carboxyl, so that the graphene oxide has good compatibility. The graphene oxide is modified by a modifier to prepare a graphene gel material, which effectively improves the overall adsorption performance, thermal stability and mechanical strength of the system, thereby further improving the overall stability of the glass fiber paper.

[0018] Preferably, the graphene oxide aerogel is prepared by the following method: Graphene oxide is dissolved in a dimethylacetamide solution, and ultrasonic treatment is performed to obtain a graphene oxide dispersion. A modifier is added to the graphene oxide dispersion, and the dispersion is stirred after ultrasonic treatment. Subsequently, dicyclohexylcarbodiimide and dimethylaminopyridine are added, and the mixture is stirred and dried to obtain a modifier composite graphene oxide. The modifier composite graphene oxide is mixed with water, and ethylenediamine is added. The mixture is washed after vacuum heating and freeze-dried to obtain a modified graphene oxide aerogel.

[0019] Preferably, the modifier comprises lauric acid.

[0020] By adopting the above technical scheme, lauric acid is a medium-chain fatty acid, which is grafted onto the surface of graphene oxide through an esterification reaction, and a modified graphene oxide gel modified with lauric acid is obtained at the same time. Lauric acid is evenly distributed in the gaps, and the thermal stability and adsorption properties of the graphene aerogel are greatly improved, so that the performance of the prepared glass fiber paper is further improved.

[0021] Preferably, the mass ratio of the graphene oxide to lauric acid is 1:(0.6-0.8).

[0022] By adopting the above technical solution, preferably the mass ratio between graphene oxide and lauric acid is within the above range, the comprehensive performance of the prepared modified graphene oxide aerogel can be further improved.

[0023] In a second aspect, the present application provides a method for preparing glass fiber paper for a dehumidification wheel, using the following technical solution: A method for preparing glass fiber paper for a dehumidification wheel, comprising the following steps: Glass fiber, wood pulp, magnesium oxide, polyvinyl alcohol fiber, coconut shell fiber, modified graphene oxide gel, modified biochar and a dispersant are mixed, stirred and formed, and then dried to obtain glass fiber paper.

[0024] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application prepares glass fiber paper by compounding glass fiber, wood pulp, dispersant, magnesium oxide, polyvinyl alcohol fiber, and coconut shell fiber, which has good strength and good adsorption performance, and also has good stability in a hot and humid environment. At the same time, modified graphene oxide gel and modified biochar components are added to the system. The modified graphene oxide gel can further improve the strength and stability of the system, and the modified biochar can further improve the adsorption performance of the system. 2. The modified biochar component is prepared by bamboo chips, calcium chloride and urea. The doping of urea promotes the nitrogen atoms to obtain carbon skeletons in the form of pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen, so that the richness of nitrogen functional groups on the surface of biochar is improved. Calcium chloride is used as an active agent to further modify the biochar. The performance of the biochar is further improved by low-temperature air oxidation technology, so as to improve the comprehensive performance of the modified glass fiber paper. 3. Modified graphene oxide aerogel is prepared by lauric acid. Lauric acid is a medium-chain fatty acid. After being grafted onto the surface of graphene oxide through an esterification reaction, lauric acid-modified graphene oxide aerogel is prepared at the same time, so that lauric acid can be evenly distributed in the pores, thereby greatly improving the thermal stability and adsorption performance of the graphene aerogel, thereby improving the comprehensive performance of the prepared glass fiber paper. DETAILED DESCRIPTION

[0025] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained commercially; Example 1 Preparation of modified biochar: The bamboo chips were dried at 105°C for 48 hours, then crushed by a pulverizer, and passed through a 100-mesh sieve to obtain the crushed bamboo chips. 17.24 g of the crushed bamboo chips were placed in a quartz ark, placed in the middle of a tube furnace, and nitrogen was introduced into the furnace at a rate of 100 mL / min for 15 minutes. Then, the temperature was increased to 450°C at a rate of 10°C / min, and maintained for 30 minutes. After heating, the mixture was naturally cooled to 25°C under nitrogen protection and sealed to obtain the treated bamboo chips for use. 17.24 g of anhydrous calcium chloride, the above-mentioned treated bamboo chips and 200 g of ethanol were mixed, and magnetic stirring was performed for 24 hours to obtain a mixed solution. The mixed solution was then dried at 105°C for 48 hours, and calcium chloride-treated bamboo chips were obtained after grinding; the calcium chloride-treated bamboo chips were mixed with 15.52g of urea, placed in a quartz ark, and then placed in the middle of a tube furnace, and nitrogen was introduced at a rate of 100m / min for 15 minutes, and then heated to 800°C at a heating rate of 10°C / min and maintained for 60 minutes, and then naturally cooled to 350°C, the nitrogen was turned off, oxygen was introduced, and the temperature was maintained at 350°C for 230 minutes, and then the oxygen was turned off, nitrogen was introduced, and it was cooled to 25°C in a nitrogen-protected atmosphere, and the modified biochar was obtained after being taken out.

[0026] Preparation of modified graphene oxide aerogel: 12.5 g of graphene oxide was dissolved in 500 g of dimethylacetamide solution and ultrasonically treated for 5 min to obtain a graphene oxide dispersion. 5 g of lauric acid was added to the graphene oxide dispersion, ultrasonicated for 1 h, and then stirred at 25 ° C for 24 h to completely dissolve the lauric acid. Subsequently, 125 g of dicyclohexylcarbodiimide and 25 g of dimethylaminopyridine were added, stirred at 25 ° C for 48 h and dried to obtain lauric acid composite graphene oxide A. The above method was repeated to prepare lauric acid composite graphene oxide B. The difference between lauric acid composite graphene oxide B is that the amount of lauric acid added is 10 g. Lauric acid composite graphene oxide A and lauric acid composite graphene oxide B were mixed and added to deionized water, 800 g of ethylenediamine was added, and vacuum heated at 85 ° C for 12 h, then washed with deionized water, and freeze-dried at -20 ° C for 12 h to obtain modified graphene oxide aerogel.

[0027] Preparation of fiberglass paper: 60 g of glass fiber, 25 g of wood pulp, 15 g of magnesium oxide, 30 g of polyvinyl alcohol fiber, 22 g of coconut shell limit, 14 g of modified graphene oxide gel, 20 g of modified biochar and 10 g of dispersant were mixed, stirred for 30 minutes, and then formed and dried to obtain glass fiber paper.

[0028] Example 2 Preparation of modified biochar: The bamboo chips were dried at 105°C for 48 hours, then crushed by a pulverizer, and passed through a 100-mesh sieve to obtain the crushed bamboo chips. 16.13 g of the crushed bamboo chips were placed in a quartz ark, placed in the middle of a tube furnace, and nitrogen was introduced into the furnace at a rate of 100 mL / min for 15 minutes. Then, the temperature was increased to 450°C at a rate of 10°C / min, and maintained for 30 minutes. After heating, the mixture was naturally cooled to 25°C under nitrogen protection and sealed to obtain the treated bamboo chips for use. 16.13 g of anhydrous calcium chloride, the above-mentioned treated bamboo chips and 200 g of ethanol were mixed, and magnetic stirring was performed for 24 hours to obtain a mixed solution. The mixed solution was then dried at 105°C for 48 hours, and calcium chloride-treated bamboo chips were obtained after grinding; the calcium chloride-treated bamboo chips were mixed with 17.74 g of urea, placed in a quartz ark, and then placed in the middle of a tube furnace, and nitrogen was introduced at a rate of 100 m / min for 15 minutes, and then heated to 800°C at a heating rate of 10°C / min and maintained for 60 minutes, and then naturally cooled to 350°C, the nitrogen was turned off, oxygen was introduced, and the temperature was maintained at 350°C for 250 minutes, and then the oxygen was turned off, nitrogen was introduced, and it was cooled to 25°C in a nitrogen-protected atmosphere, and the modified biochar was obtained after being taken out.

[0029] Preparation of modified graphene oxide aerogel: 11.11 g of graphene oxide was dissolved in 500 g of dimethylacetamide solution, and ultrasonic treatment was performed for 5 min to obtain a graphene oxide dispersion. 5.93 g of lauric acid was added to the graphene oxide dispersion, and ultrasonic treatment was performed for 1 h. Then, the lauric acid was completely dissolved at 25 ° C. Then, 111.1 g of dicyclohexylcarbodiimide and 22.22 g of dimethylaminopyridine were added, and the mixture was stirred at 25 ° C. for 48 h and dried to obtain lauric acid composite oxide. Modified graphene A, repeat the above method to prepare lauric acid composite graphene oxide B, the difference of lauric acid composite graphene oxide B is that the amount of lauric acid added is 11.85 g; lauric acid composite graphene oxide A and lauric acid composite graphene oxide B are mixed and added to deionized water, 800 g of ethylenediamine is added, and the mixture is vacuum heated at 85 ° C for 12 h, then washed with deionized water, and freeze-dried at -20 ° C for 12 h to obtain modified graphene oxide aerogel.

[0030] Preparation of fiberglass paper: 80 g of glass fiber, 35 g of wood pulp, 25 g of magnesium oxide, 36 g of polyvinyl alcohol fiber, 28 g of coconut shell limit, 20 g of modified graphene oxide gel, 24 g of modified biochar and 12 g of dispersant were mixed, stirred for 30 minutes, and then formed and dried to obtain glass fiber paper.

[0031] Example 3 Preparation of modified biochar: The bamboo chips were dried at 105°C for 48 hours, then crushed by a pulverizer, and passed through a 100-mesh sieve to obtain the crushed bamboo chips. 16.67 g of the crushed bamboo chips were placed in a quartz ark, placed in the middle of a tube furnace, and nitrogen was introduced into the furnace at a rate of 100 mL / min for 15 minutes. Then, the temperature was increased to 450°C at a rate of 10°C / min, and maintained for 30 minutes. After heating, the mixture was naturally cooled to 25°C under nitrogen protection and sealed to obtain the treated bamboo chips for use. 16.67 g of anhydrous calcium chloride, the above-mentioned treated bamboo chips and 200 g of ethanol were mixed, and magnetic stirring was performed for 24 hours to obtain a mixed solution. The mixed solution was then dried at 105°C for 48 hours, and calcium chloride-treated bamboo chips were obtained after grinding; the calcium chloride-treated bamboo chips were mixed with 16.67g of urea, placed in a quartz ark, and then placed in the middle of a tube furnace, and nitrogen was introduced at a rate of 100m / min for 15min, and then heated to 800°C at a heating rate of 10°C / min, and maintained for 60min, and then naturally cooled to 350°C, the nitrogen was turned off, oxygen was introduced, and the temperature was maintained at 350°C for 240min, and then the oxygen was turned off, nitrogen was introduced, and it was cooled to 25°C in a nitrogen-protected atmosphere, and the modified biochar was obtained after being taken out.

[0032] Preparation of modified graphene oxide aerogel: 11.765 g of graphene oxide was dissolved in 500 g of dimethylacetamide solution, and ultrasonic treatment was performed for 5 min to obtain a graphene oxide dispersion. 5.49 g of lauric acid was added to the graphene oxide dispersion, and ultrasonic treatment was performed for 1 h. Then, the lauric acid was stirred for 24 h at 25 ° C to completely dissolve the lauric acid. Then, 117.65 g of dicyclohexylcarbodiimide and 23 g of dimethylaminopyridine were added, and the mixture was stirred for 48 h at 25 ° C and dried to obtain lauric acid composite oxide. Modified graphene A, repeat the above method to prepare lauric acid composite graphene oxide B, the difference of lauric acid composite graphene oxide B is that the amount of lauric acid added is 10.98 g; lauric acid composite graphene oxide A and lauric acid composite graphene oxide B are mixed and added to deionized water, 800 g of ethylenediamine is added, and the mixture is vacuum heated at 85 ° C for 12 h, then washed with deionized water, and freeze-dried at -20 ° C for 12 h to obtain modified graphene oxide aerogel.

[0033] Preparation of fiberglass paper: 70 g of glass fiber, 30 g of wood pulp, 20 g of magnesium oxide, 33 g of polyvinyl alcohol fiber, 25 g of coconut shell limit, 17 g of modified graphene oxide gel, 22 g of modified biochar and 11 g of dispersant were mixed, stirred for 30 minutes, and then molded and dried to obtain glass fiber paper.

[0034] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that when preparing the modified biochar, 20 g of bamboo chips, 20 g of calcium chloride and 10 g of urea are added.

[0035] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that when preparing the modified biochar, 14.29 g of bamboo chips, 14.29 g of calcium chloride and 21.42 g of urea are added.

[0036] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that when preparing the modified biochar, the oxygen is introduced and maintained for 200 minutes.

[0037] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that when preparing the modified biochar, the oxygen is introduced and maintained for 300 minutes.

[0038] Example 8 Example 8 is based on Example 3. The difference between Example 6 and Example 3 is that when preparing the modified biochar, only nitrogen treatment is performed, and oxygen treatment is not performed.

[0039] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that, when preparing the modified graphene oxide gel, the graphene oxide used in the preparation of lauric acid composite graphene oxide A is 14.285 g, and the lauric acid is 3.81 g. The graphene oxide used in the preparation of lauric acid composite graphene oxide B is 14.285 g, and the lauric acid is 7.62 g.

[0040] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that when preparing the modified graphene oxide gel, the graphene oxide used in the preparation of lauric acid composite graphene oxide A is 10 g and the lauric acid is 6.67 g, and the graphene oxide used in the preparation of lauric acid composite graphene oxide B is 10 g and the lauric acid is 13.33 g.

[0041] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that lauric acid is replaced by tetradecanol when preparing the modified graphene oxide gel.

[0042] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that lauric acid is replaced by capric acid when preparing the modified graphene oxide gel.

[0043] Comparative Example 1 Comparative Example 1 is based on Example 3. In Comparative Example 1, the modified biochar is prepared without using nitrogen or oxygen for treatment.

[0044] Comparative Example 2 Comparative Example 2 is based on Example 3, and in Comparative Example 2, the modified biochar is replaced with ordinary bamboo chips.

[0045] Comparative Example 3 Comparative Example 3 is based on Example 3, and in Comparative Example 3, the modified graphene oxide gel is replaced by ordinary graphene oxide.

[0046] Performance testing The following performance tests were performed on the samples of Examples 1-12 and Comparative Examples 1-3: (1) Adsorption rate performance test The sample was subjected to an adsorption test in an environment with a temperature of 25°C and a humidity of 30%. The wind speed was set to 3m / s, and the adsorption performance was tested. The moisture absorption rate (R) was balanced by the weight of the material before and after moisture absorption. The calculation formula is as follows: R = (m2-m1) / m1*100%; wherein m1 is the mass (g) of the inorganic fiber paper for the drying dehumidification wheel, and m2 is the mass (g) of the inorganic fiber paper for the dehumidification wheel after adsorption for 15 minutes.

[0047] (2) Tensile strength performance test The longitudinal tensile strength of the samples was tested 3 times for each sample, the average value was taken, and the test results were filled in Table 1.

[0048] (3) Test of resistance to moisture and heat aging The samples were aged at 65°C and 95% humidity for 8 h, and then the longitudinal tensile strength test was performed again. Each sample was tested 3 times, and the average value was taken. The test results were filled in Table 1.

[0049] Table 1 Performance test results of Examples 1-12 and Comparative Examples 1-3 Data analysis Combined with Table 1, it can be seen that the moisture absorption equilibrium rates of Examples 1-3 are all 47% or above, indicating that the glass fiber paper prepared in the present application has good adsorption performance, the longitudinal tensile strengths of Examples 1-3 are all 5N / mm or above, indicating that the glass fiber prepared in the present application has good tensile strength, and the tensile strengths of Examples 1-3 after wet heat aging are all 4.5N / mm or above, and the change rates are all 10% or below, indicating that the glass fiber paper prepared in the present application has good moisture and heat resistance.

[0050] In Examples 4 and 5, when preparing modified biochar, the mass ratios of bamboo chips, calcium chloride and urea are not within the range specified in the present application. When the urea content is too little, the modification ability of bamboo chips is difficult to be further improved, the specific surface area of ​​bamboo charcoal is difficult to be further improved, the structural growth of the carbon skeleton is difficult to be further promoted, the disorder of the carbon surface is difficult to be improved, and the richness of the functional groups on the surface is difficult to be further improved, and the compatibility in the system is reduced. When the urea content is too much, the pore structure of the biochar is blocked, thereby reducing the stability of the biochar. Therefore, the performance of Examples 4 and 5 is further reduced.

[0051] When preparing modified biochar in Example 6 and Example 7, the retention time after the introduction of oxygen is not within the range specified in the present application. When the time for introducing oxygen is too short, the micropore surface area of ​​the biochar system is difficult to further increase, affecting the adsorption performance. When the time for introducing oxygen is too long, the biochar has too many pore structures, which will affect the overall stability of the biochar, thereby reducing the performance of the biochar.

[0052] In Example 8, the biochar was not treated with oxygen, which made it difficult to further promote the growth of the pore structure of the biochar, and thus affected the adsorption performance of the biochar.

[0053] The mass ratios of lauric acid and graphene oxide in Examples 9 and 10 are not within the range defined in the present application. When the content of lauric acid is too little, the connection between lauric acid and graphene oxide is poor, and it is difficult to further promote the enhancement of the interaction force, thereby affecting the stability of the system. When the content of lauric acid is too much, defects, free radicals and other irregularities will appear on the surface of graphene oxide, which will affect the overall thermal stability and supporting performance of the system. Therefore, the performance of Examples 9 and 10 are both reduced.

[0054] In both Example 11 and Example 12, lauric acid was replaced. However, the thermal stability of tetradecanol and capric acid was worse than that of lauric acid, and the performance of the prepared graphene oxide gel was reduced. Therefore, the performance of Example 11 and Example 12 was reduced.

[0055] In Comparative Example 1, the biochar was not treated with nitrogen or oxygen, and the porosity of the biochar produced by ordinary pyrolysis was difficult to be further improved, so the performance of Comparative Example 1 was reduced.

[0056] In Comparative Example 2, the modified biochar was replaced with ordinary bamboo chips. The pore structure of unmodified ordinary bamboo chips is difficult to be further improved, and the richness of surface functional groups is difficult to be further improved. Therefore, the adsorption degree and stability of ordinary bamboo chips are difficult to be improved, so the performance of Comparative Example 2 is reduced.

[0057] In Comparative Example 3, the modified graphene oxide gel is replaced by ordinary graphene oxide. The thermal stability of ordinary graphene oxide is difficult to be further improved, and its compatibility in the system is poor, so the stability of the prepared glass fiber paper is reduced.

[0058] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A glass fiber paper for a dehumidification wheel, characterized in that: The composition comprises the following components in parts by weight: 60-80 parts of glass fiber, 25-35 parts of wood pulp, 15-25 parts of magnesium oxide, 30-36 parts of polyvinyl alcohol fiber, 22-28 parts of coconut shell fiber, 20-24 parts of modified biochar, 14-20 parts of modified graphene oxide gel, and 10-12 parts of dispersant.

2. The glass fiber paper for a dehumidification wheel according to claim 1, characterized in that: The modified biochar comprises bamboo chips, calcium chloride and urea.

3. The glass fiber paper for a dehumidification wheel according to claim 2, characterized in that: The modified biochar is prepared by the following method: The bamboo chips are dried, crushed and sieved, placed in a quartz ark, placed in the middle of a tube furnace, nitrogen is introduced, the temperature is increased, and the chips are cooled to obtain treated bamboo chips; anhydrous calcium chloride, treated bamboo chips and ethanol are mixed and stirred to obtain a mixed solution, which is then dried and ground to obtain calcium chloride treated bamboo chips; the calcium chloride treated bamboo chips are mixed with urea, placed in a quartz ark, and then placed in the middle of a tube furnace to perform nitrogen and oxygen treatment to obtain modified biochar.

4. The glass fiber paper for a dehumidification wheel according to claim 3, characterized in that: The mass ratio of the bamboo chips, calcium chloride and urea is 1:1:(0.9-1.1).

5. The glass fiber paper for a dehumidification wheel according to claim 2, characterized in that: The nitrogen and oxygen treatment specifically comprises the following steps: Nitrogen is introduced to heat and maintain for a period of time, then cooled, the nitrogen is turned off, oxygen is introduced, and the constant temperature is maintained for 230-250 minutes, then the oxygen is turned off, nitrogen is introduced again, and the mixture is cooled in a nitrogen-protected atmosphere, and the modified biochar is obtained after being taken out.

6. The glass fiber paper for a dehumidification wheel according to claim 1, characterized in that: The graphene oxide gel comprises graphene oxide and a modifier.

7. The glass fiber paper for a dehumidification wheel according to claim 6, characterized in that: The graphene oxide aerogel is prepared by the following method: dissolving graphene oxide in a dimethylacetamide solution, ultrasonically treating to obtain a graphene oxide dispersion, adding a modifier to the graphene oxide dispersion, stirring after ultrasonic treatment, subsequently adding dicyclohexylcarbodiimide and dimethylaminopyridine, stirring and drying to obtain a modifier composite graphene oxide, mixing the modifier composite graphene oxide with water, adding ethylenediamine, vacuum heating and then washing, and freeze-drying to obtain a modified graphene oxide aerogel.

8. The glass fiber paper for a dehumidification wheel according to claim 7, characterized in that: The modifying agent includes lauric acid.

9. The glass fiber paper for a dehumidification wheel according to claim 8, characterized in that: The mass ratio between the graphene oxide and lauric acid is 1:(0.6-0.8).

10. A method for preparing the glass fiber paper for the dehumidification wheel according to claim 1, characterized in that: The steps include: Glass fiber, wood pulp, magnesium oxide, polyvinyl alcohol fiber, coconut shell fiber, modified graphene oxide gel, modified biochar and a dispersant are mixed, stirred and formed, and then dried to obtain glass fiber paper.